A pragmatic analysis of deictic expressions used in the IELTS speaking test - Fadi Al-Khasawneh (Training, Language and Culture)
This study investigates the role of deictic expressions in the IELTS speaking test, addressing a gap in research on how test-takers across proficiency levels use deixis in spoken language assessment. While previous studies have examined general discourse features in language testing, little attention has been given to the frequency, functions, and distribution of deixis in assessing spoken proficiency. The study analysed a corpus of 30 IELTS speaking test transcripts, covering proficiency levels from low-intermediate to advanced. Using Levinson’s classification of deixis, the study employed quantitative frequency analysis and qualitative discourse analysis to examine variations in the use of personal, temporal, and spatial deixis. The findings revealed that personal deixis was the most frequently used, followed by temporal and spatial deixis. However, the results of One-Way ANOVA test showed no significant differences in deixis usage across proficiency levels. These findings contribute to English language teaching and assessment by highlighting how deixis functions in test-taker discourse, offering insights for IELTS preparation and speaking proficiency evaluation. The study indicates the need for further exploration of discourse features in language assessment.